Low breeding success of the little egret (Egretta garzetta) near residential areas and in colonies exposed to gales: a comparison of colony in Sichuan, Southwest China, with literature. Issue 3 (4th May 2019) - Pang, Rui Hua; Yu, Tong Lei; Busam, Michael
ABSTRACT: The breeding biology of the little egret ( Egretta garzetta ) was studied in 20 nests within the mixed-species breeding colonies at Nanchong, Sichuan, Southwest China, in 2006. By measuring a set of physical characteristics of vegetation at the nests and at a set of 20 randomly chosen sites we showed that birds preferentially used taller trees in areas with fewer shrubs of higher species diversity. Nests at lower locations in trees had marginally lower hatching success due to their destruction by humans; this destruction contributed marginally significantly to lowering of the total nesting success in all studied nests. Although gale winds also had a negative effect on breeding success, the anthropogenic influences were a greater factor in reproductive failure. We found similar effects in our review of literature on breeding success of the little egret from various geographical areas. Our results may be of use by conservation organizations in their actions to protect colonies of the little egret.